Breakfast Frequency and Chronic Inflammation in Chinese Adults (P18-051-19). (13th June 2019) - Zhu, Siwei; Cui, Liufu; Zhang, Xinyuan; Shu, Rong; Tucker, Katherine; Wu, Shouling; Gao, Xiang
Abstract: Objectives: Previous studies have shown that regular breakfast consumption was associated with lower risk of cardiovascular disease (CVD), but this remains controversial. Chronic inflammation is a well-established risk factor for cardiovascular disease. We, thus, examined whether breakfast frequency was associated with inflammation, assessed by high sensitivity C-reactive protein (CRP) concentration, among individuals without CVD. Methods: Included were 71, 748 participants of the Kailuan Study, an ongoing Chinese cohort, who were free of CVD and cancer.Breakfast frequency was assessed via questionnaire in 2014, and participants were categorized into four groups in the current analysis –no breakfast, 1–2 times/week, 3–5 times/week, or breakfast every day. Plasma CRP concentration was measured using a high-sensitivity, particle-enhanced immunonephelometry assay. General linear models were used to calculate adjusted means with 95% confidence intervals (CIs) for CRP, and logistic regression models were used to calculate odds ratios (ORs) of chronic inflammation (CRP concentration ≥1.0 mg/L or ≥3.0 mg/L), across the four breakfast groups. We adjusted for age, sex, diet quality score, body mass index, education level, occupation type, marital status, smoking status, systolic blood pressure, fasting blood glucose, low-density lipoprotein cholesterol and high-density lipoprotein cholesterol in the models. Results: Greater breakfast frequency was associated with lower CRP concentration (P-trend < 0.001). Adjusted mean CRP was 1.40 mg/L (95% CIs: 1.33, 1.48) for the "no breakfast" group and 1.07 mg/L (95% CIs: 1.02, 1.12) for the "breakfast everyday" group (P-difference < 0.001). Similar results were observed for the odds of chronic inflammation. The adjusted OR for CRP ≥ 1.0 mg/Lwas 2.55 (95% CIs: 2.39, 2.72) and for CRP ≥ 3.0 mg/L was1.21 (1.12, 1.30) for the "no breakfast" group, relative to the "breakfast everyday" group (P-trend < 0.001, Figure 1) Conclusions: Skipping breakfast was associated with chronic inflammation among individuals without CVD. Funding Sources: The Institute for CyberScienceSeedGrantProgram, Penn State University and the start-up grant from the college of health and human development and the department of nutritional sciences, Penn State University. Supporting Tables, Images and/or Graphs: